Pola Konsumen dalam Mengakses Website (Traffic sources) Rumah Sakit Di Depok - Satar, Yuli Prapancha; Vera, Nur Arini Batubara (Jurnal Vokasi Indonesia, 2016)
Marketing is a company’s active effort of to introduce the company and their products to its consumers. The rapid growth of technology, especially internet, encourage the use of the website in marketing field. Website complements in conventional marketing such as TV, radio, newspapers, magazines, electronic media, banners, billboards, personal relationships, etc. There are six ways for consumers to access company’s website, typing website address directly, through a link on another website, using through search engine, through social link, via email link received by consumers, and through an advertising link viewed by consumers. This study aims to determine patterns or compositions used by visitors to access the nine hospital’s websites in Depok. The method of collecting data using secondary data obtained from www.pagerank.net. Data was taken on April 25, 2016. Results of the study revealed that the pattern of consumers in accessing hospital’s website in Depok is through search engines, followed by a link on another website and typing the website address directly.The other three ways are not used as traffic sources.